Application of the Theory of Multiple Intelligences to Digital Systems Teaching - Costa Neto, Alvaro; Marranghello, Norian; Pereira, Aledir Silveira (Anais do Workshop sobre Educação em Computação (WEI); 2010: Anais do XVIII Workshop sobre Educação em Computação, 2010)
Transmission of knowledge is of extreme importance for the evolution of a society. For centuries, teaching processes have undergone considerable evolution to reach the current stage, creating new theories on the way. The Theory of Multiple Intelligences, by Howard Gardner, which has been chosen as the theoretic guideline of the work presented in this paper, states that the human intellect can be divided into areas of activity called intelligences. Stimulating other intelligences outside those naturally related to a discipline is a challenging task. To propose a solution to this challenge, this work presents three tools that are designed to help the teacher construct additional classes, along with a guideline for a course of Digital Systems.